AIDS and Social Exclusion: Personality Features or Adaptive Behaviors? - Pérez San Gregorio, Mª Ángeles; Flores Sarazúa, Enrique; Borda Más, Mercedes (The Spanish Journal of Psychology, 2005)
The purpose of this survey is to detect common personality features in people infected with AIDS who have a case history of drug addiction and who live in a situation of social exclusion. The sample comprised 105 male participants from the Autonomous Community of Andalusia, divided into 4 groups: (a) 30 men with AIDS, having an intravenous drug addiction case history and who live in a condition of social exclusion; (b) 30 men with IVDA case history, also living in a situation of social exclusion; (c) 15 men in a social exclusion condition; and (d) 30 men in a condition of social adaptation. The evaluation instruments were an author-designed semi-structured interview and the Multiaxial Clinical Inventory (MCMI-II; Millon, 1987). Although some differences were found, the results indicate that there is no specific personality profile in the “social exclusion” population. People in a condition of social exclusion (AIDS, drug addicts, and poor people) may obtain similar scores in the variables studied, but there is no clear specific personality profile in the excluded population, although there may be certain situations in which the segregated groups present similar behaviors. Furthermore, these behaviors do not always correspond to personality features but are adaptive responses to a harsh and complex reality.